Structuralist and behavioral macroeconomics - Skott, Peter (New York Cambridge University Press, 2023)
Mainstream macroeconomics is founded on the idea of perfectly rational representative agents. Yet there is a growing realization that economic theories based on such agents are inadequate guides to real-world decision making. The behavioural evidence has had significant impacts on microeconomics but the same cannot be said of macroeconomics. This book is part of the movement to do for macroeconomics what behavioural thinking has done for microeconomics. Using behavioural evidence and insights from Keynesian and institutionalist traditions, it presents an empirically grounded alternative to the paradigm that currently dominates macroeconomic theory.